Development of preservation by processing technologies of BAU kul (Journal of the Bangladesh Agricultural University, 2014)
This study reports on processing of jam, jelly and chutney from BAU kul and assessing the products shelf life and food value. This study was conducted in the laboratory of the Department of Food Technology and Rural Industries, Bangladesh Agricultural University, Mymensingh. The fruits were collected from the local market and the pulp was extracted and analyzed for proximate composition. The proximate analysis of BAU kul pulp showed 86.12% moisture, 19.00% TSS, 06.04% reducing sugar, 15.16 % non-reducing sugar, 21.20% total sugar, 01.35% ash, 04.50PH, 00.44% acidity and 65mg/100g vitamin C. A total three types of products each with 3 different formulations were prepared and packed in appropriate packaging for storage studies. Products were stored at room temperatures and change their physical and chemical condition during storage was observed at an interval of 30 days for a period of four months. A taste panel consisting 10 panelists studied the acceptability of the samples. The consumers preferences were measured by statistical analysis of the scores obtained from the responses of the taste panel. Among the samples jam of (TSS 65.50%, pectin 0.5%, PH 3.10), jelly of (TSS 66.50%, pectin 0.5% and PH 3.15) and chutney of (TSS 65.5%, PH 3.20) were awarded the highest scores by the panelists. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21404 J. Bangladesh Agril. Univ. 12(1): 143-152, June 2014